2015
DOI: 10.1088/0963-0252/24/5/053001
|View full text |Cite
|
Sign up to set email alerts
|

Microwave discharges at low pressures and peculiarities of the processes in strongly non-uniform plasma

Abstract: Microwave discharges (MD) are widely used as a source of non-equilibrium low pressure plasma for different applications. This paper reviews the methods of microwave plasma generation at pressures from 10 −2 approximately to 30 kPa with centimeter-millimeter wavelength microwaves on the basis of scientific publications since 1950 up to the present. The review consists of 16 sections. A general look at MDs and their application is given in the introduction, together with a description of a typical block-schema o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(38 citation statements)
references
References 273 publications
(305 reference statements)
0
34
0
2
Order By: Relevance
“…The BPs of C 2 (0,0), C 2 (0,1), and C 2 (1,0) band R 2 branch lines, recorded from Ar + 20% C 2 H 2 MIP, are shown in Figure 10. The BPs of CH(0-0, B 2 Σ − -X 2 Π) band Q 1 branch lines and CH(0-0, A 2 Δ-X 2 Π) band R 2 branch lines obtained for the same FIGURE 10 The Boltzmann plots (BPs) of C 2 (0,0), C 2 (0,1), and C 2 (1,0) band R 2 branch lines, recorded from Ar + 20% and He+20% C 2 H 2 microwave-induced plasma (MIP)…”
Section: The T Rot and T Vib Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BPs of C 2 (0,0), C 2 (0,1), and C 2 (1,0) band R 2 branch lines, recorded from Ar + 20% C 2 H 2 MIP, are shown in Figure 10. The BPs of CH(0-0, B 2 Σ − -X 2 Π) band Q 1 branch lines and CH(0-0, A 2 Δ-X 2 Π) band R 2 branch lines obtained for the same FIGURE 10 The Boltzmann plots (BPs) of C 2 (0,0), C 2 (0,1), and C 2 (1,0) band R 2 branch lines, recorded from Ar + 20% and He+20% C 2 H 2 microwave-induced plasma (MIP)…”
Section: The T Rot and T Vib Resultsmentioning
confidence: 99%
“…Electron impact is the main channel of heavy particle excitation and ionization near the electrode, while the secondary processes with the participation of excited particles may contribute as well in the plasma ball region. [8][9][10] In addition, kinetic modelling of nitrogen plasma showed that all observed bands are excited by electron impact owing to a high electric field near the antenna. [9] Previously, the MIP source was employed for diamond growth on heated silicon substrates in the H 2 /CH 4 /O 2 mixture at 20 mbar [11] as well as for T g and T vib measurements using Swan bands emitted from C7-C16 alkane (C n H 2n+2 ) discharges in the liquid phase.…”
Section: Introductionmentioning
confidence: 99%
“…In general, microwave discharges can stably produce low-temperature plasmas even at high pressure compared to RF and VHF discharges. A microwave-excited plasma (MWP) has some advantages over other types of plasma sources as it has a wide range of operating pressures from 10 −2 Pa up to pressures exceeding the atmospheric pressure, allows a wide range of plasma absorbed power, and eliminates the possibility of contamination of the plasma and treated surfaces through electrode erosion because of the electrode less discharge [30]. However, previous MWP sources providing nitrogen radicals such as electron cyclotron resonance plasmas [9,11,21,23], tubular-microwave-reactor plasmas [12,13,17,21,23], and resonant-cavity-downstream plasmas [18] impose limitations on enlarging the processing area and reducing the microwave power at high pressure because of a lack in structural flexibility and expandability of rectangular waveguides, external magnetic field controllers, tubular reactors, and resonance cavities.…”
Section: Introductionmentioning
confidence: 99%
“…The design of MWDs has considerable influence on its operation range, for example, available pressure ranges, types of useable feed gases, power dissipation processes, excited discharge volumes, and also vacuum compatibility, and might strongly influence the discharge parameters, including the plasma composition, gas temperature, and electron energy distribution function. The main constructional and operational principles of MWDs developed for reduced pressures are reviewed by Lebedev . During the last decade, much progress has been achieved, in particular, in the generation and sustenance of atmospheric‐pressure MWDs.…”
Section: Introductionmentioning
confidence: 99%